Intertextual Adaptation of the Story of the Prophet Joseph in Mocoan Lontar Yusup Banyuwangi - Rina Najiha; Fawaizul Umam; Matkur Matkur (Eastasouth Institute, 2026)
The story of the Prophet Yusuf in the Qur'an (QS. Surat Yusuf) has been transformed into a sacred text of Lontar Yusup culture among the people of the Osing tribe, Banyuwangi. This research aims to unravel the process of negotiation and cultural adaptation using an intertextual literary criticism approach. Through the descriptive qualitative method, QS. Yusuf's letter is positioned as a hypogram and Yusup's Lontar manuscript as a transformation text. The results of the study show that local copyists do not just carry out literal translations, but practice cultural transposition through three main mechanisms: narrative expansion that domesticates the geographical setting into agrarian cosmology and the ethics of the archipelago palace; modification of characterization from a pure prophetic figure to an ideal knight figure who walks the path of Sufism; as well as theological contextualization through the practice of performing the ritual of mocking the night before. In conclusion, the intertextual relationship in this tradition is not a syncretism that reduces the purity of the value of monotheism, but a form of civilizational negotiation and a harmonious cultural da'wah strategy. These findings confirm that sacred texts can be earthed as functional moral guides without having to uproot the roots of indigenous peoples' sociocultural identities.